Omni and Multi-Channel: Relationship with Utilitarian/Hedonic Benefits, Shopping Value and Channel Patronage - Kokku, Randheer (International Review of Management and Marketing, 2021)
This study makes an attempt to examine channel patronage, a narrow research gap from literature in the omni and multichannel concept, additionally it has taken up shopping value, utilitarian and hedonic benefits. It examined the characteristics and relationship of omni and multi-channel. It observed whether channels deliver shopping value to customers. It found shopping value is created have significant relationship with utilitarian and hedonic benefits. Ultimately this study fills the research gap by throwing light on why customers show patronage for a retail channel and does shopping value effect it. Reflective first and second order model was used. Both EFA and CFA were performed. Average variance extracted, composite reliability, Cronbach’s alpha, cross loadings and Fornell and Lacker’s values were used to assess convergent and discriminant validity for measurement model. Path coefficient was used to assess structural model. Validation of structural model was done using R2, f2 and Q2. It was found that respondents opine omni is different and better than multi-channel. Utilitarian and hedonic have relationship with both, but are better in omni than multi-channel. Independently, shopping value and customer patronage have relationship with utilitarian and hedonic; omni and multi-channels; but they are better in hedonic than utilitarian; and omni than multi-channel. Customer patronage has relationship with shopping value and is better in omni than multi-channel when moderated by later. Keywords: Omni Channel, Multi-Channel, Utilitarian, Hedonic, Shopping Value, Retail Channel Patronage. JEL Classifications: M31, M39 DOI: https://doi.org/10.32479/irmm.11215